HIV-1 provirus transcription and translation in macrophages differs from pre-integrated cDNA complexes and requires E2F transcriptional programs. Issue 1 (31st December 2022) - Lim, Albebson L.; Moos, Philip; Pond, Christopher D.; Larson, Erica C.; Martins, Laura J.; Szaniawski, Matthew A.; Planelles, Vicente; Barrows, Louis R.
ABSTRACT: HIV-1 cDNA pre-integration complexes persist for weeks in macrophages and remain transcriptionally active. While previous work has focused on the transcription of HIV-1 genes; our understanding of the cellular milieu that accompanies viral production is incomplete. We have used an in vitro system to model HIV-1 infection of macrophages, and single-cell RNA sequencing (scRNA-seq) to compare the transcriptomes of uninfected cells, cells harboring pre-integration complexes (PIC), and those containing integrated provirus and making late HIV proteins. scRNA-seq can distinguish between provirus and PIC cells because their background transcriptomes vary dramatically. PIC cell transcriptomes are characterized by NFkB and AP-1 promoted transcription, while transcriptomes of cells transcribing from provirus are characterized by E2F family transcription products. We also find that the transcriptomes of PIC cells and Bystander cells (defined as cells not producing any HIV transcript and thus presumably not infected) are indistinguishable except for the presence of HIV-1 transcripts. Furthermore, the presence of pathogen alters the transcriptome of the uninfected Bystander cells, so that they are distinguishable from true control cells (cells not exposed to any pathogen). Therefore, a single cell comparison of transcriptomes from provirus and PIC cells provides a new understanding of the transcriptional changes that accompany HIV-1 integration.